Development of Angle Control System Application Using Python - Phutthanukun, Warinda; Chayratsami, Pornpimon (My University, 2019)
This paper presents an educational tool for feedback control system class. An application is created using Python for simulating the DC motor angle control. The control method used in the application is Proportional-Integral-Derivative (PID) controller. Inputs of the application consist of motor parameters obtained by theoretically modeling the system, the PID control constant gains, and a desired angle. Outputs are the displays of a root locus plot, a step response plot, and an animation of the motor movement. The results of using the application in the feedback control class indicate that the application helps enhancing student's understanding in the PID control concept and also helps students to visualize the system behavior practically.
Keywords: Application; Control System; GUI; Python